Experimental kinetics of infection induced by Yersinia pseudotuberculosis isolated from stock animals - Martins, Carlos Henrique Gomes [UNESP]; Falcão, Deise Pasetto [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2004)
The course of in vivo infection of five isolates of Yersinia pseudotuberculosis was followed for three weeks in Swiss mice. The strains were isolated from diarrheic and normal feces and mesenteric lymph nodes of healthy and sick stock animals. Four strains of serogroup O:3 and one of serogroup O:1a, with and without the virulence plasmid, were inoculated intragastrically and intravenously in the mice. Groups of five animals were sacrificed at 6 h and 3, 6, 10, 15, and 21 days after inoculation, and organs and tissues were checked for possible macroscopic alterations. Development of infection was monitored at these times by performing viable bacterial counts in homogenates of selected tissues. The animals were cheked daily for clinical alterations. The results of the study showed that strains with the virulence plasmid infected organs and tissues at various times and at varying intensity by both routes of infection, the strain of type O:1a being the most invasive. Moreover, clinical and pathological alterations occurred only in animals inoculated with bacteria carrying the virulence plasmid, regardless of the route of infection.
Keywords: Yersinia pseudotuberculosis; kinetics of infection; virulence